Design and Construction of Prototype of CNC Plasma Cutting Machine Simulator 3 Axis Based on Stepper Motor and Mach3 PC Software - Asep Dharmanto; Nur Rofiq; Asep Saepudin; Aswin Domodite; Wilarso (Universitas Medan Area, 2025)
In a workshop, the machining or cutting process of plates must be done quickly and accurately, while most of them are still done manually or by hand. One of the technologies used today is the CNC (Computerized Numerical Control) machine which is one of the results of the development of machining technology that can be operated automatically and continuously, so that it can support the need for requests for complex workpiece shapes, high accuracy and in large quantities. In its processing, this workpiece is very difficult to do with a manual process or with ordinary tools. To overcome this, a CNC plasma cutting machine design was made. CNC plasma cutting is a CNC machine whose motion system can move the plasma eye or torch according to computer commands. The design of this plasma cutting machine is carried out with a design process to determine the dimensions of the machine and calculations to determine the specifications of the drive motor, with the design of the electric wiring diagram and the selection of controller selection specifications for the system. By testing the precision of the tool during the experiment. The purpose of this design is to create a CNC plasma cutting machine with easily obtainable materials and capable of carrying out complex plate cutting work with high tool precision. This CNC plasma cutting machine uses 3-axis CNC as the main driver, namely the X axis, Y axis and Z axis, and is operated with Mach3 software as a CNC machine controller and uses a stepper motor to move the axis axis. Mach3 software was chosen because it has an easy configuration because there is an auto tuning feature in determining the precision of each axis and is easy to operate, and easy to get on the internet, so that with this CNC plasma cutting machine it can help a workshop in doing sheetmetal work efficiently and accurately which in the end can save material, time and cost of work